New constraints on the multiplicity of massive young stars in Upper Scorpius - Grellmann, Rebekka; Ratzka, Th.; Köhler, Rainer; Preibisch, Th.; Mucciarelli, P. (Astronomy and astrophysics, 2015)
Context: Observations and simulations have clearly established that most stars form in multiple systems. Characterizing their properties is thus important for our understanding of the star formation process. Aims: To provide statistics about the number of companions per star over the full range of angular distances, infrared long-baseline interferometric studies can be employed to fill the gap between spectroscopic and adaptive optics searches. The Upper Scorpius OB association is a good target for such observations, because its stellar content is very well known from both spectroscopic and adaptive optics searches. Methods: We used the ESO Very Large Telescope Interferometer to perform long-baseline interferometric observations of a sample of seven B stars. Furthermore, we used ROSAT X-ray data to search for indications of low-mass companions. Results: With the interferometric observations, we find previously known companions around σ Sco and HR 6027. For the other targets we determine the parameter space in which the presence of companions can be excluded from our data. For two of the B stars in our sample, π Sco and HR 6026, the detection of X-ray emission provides indirect evidence of previously unknown low-mass companions. Conclusions: In total we find two previously unknown companions. We can exclude the presence of other unknown companions within the separation range of ~2 to ~100 mas and for a brightness ratio ≥0.1.
Gesehen am 09.11.2020